1995
DOI: 10.1037/0033-295x.102.4.751
|View full text |Cite
|
Sign up to set email alerts
|

The Weibull distribution, the power law, and the instance theory of automaticity.

Abstract: H. Colonius (1995) agreed with the fundamental tenets of the instance theory of automaticity. His article addressed the mathematical development of the theory, pointing out an error in one of two arguments that G. D. Logan (1988,1992) used to justify the choice of the Weibull as the distribution of retrieval times and suggesting an alternative argument that places different emphasis on the power function speedup and the Weibull distribution. This article attempts to clarify the problematic argument, point out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…The Wald distribution arises from a diffusion process with one absorbing boundary and has been used to explain simple (detection) behavior (Emerson, 1970;Wald, 1947), as well as to describe the firing pattern of simple neurons (Rudd, 1996). Finally, the Weibull model describes RT (under certain conditions; see Colonius, 1995) when a large number of parallel processes compete to produce a response (Logan, 1988(Logan, , 1992(Logan, , 1995.…”
Section: Methodsmentioning
confidence: 99%
“…The Wald distribution arises from a diffusion process with one absorbing boundary and has been used to explain simple (detection) behavior (Emerson, 1970;Wald, 1947), as well as to describe the firing pattern of simple neurons (Rudd, 1996). Finally, the Weibull model describes RT (under certain conditions; see Colonius, 1995) when a large number of parallel processes compete to produce a response (Logan, 1988(Logan, , 1992(Logan, , 1995.…”
Section: Methodsmentioning
confidence: 99%
“…The theory most closely tied to a power practice function is Logan's (1988Logan's ( , 1992) theory based on the minimum time for race among instance retrievals. As Logan (1995) has acknowledged, "A major goal in developing the theory was to account for the power function speedup" (p. 751). Logan's theory uses a weak learning mechanism, in comparison with other theories of skill acquisition.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Clearly, there may be alternative ways of considering a variable's influence on RT distributions that are preferable (see Van Zandt, 2000, for several examples). For example, RT distributions have also been modeled with the Weibull (Logan, 1995) and ex-Wald (Schwarz, 2001) distributions. In this study, we have demonstrated how ex-Gaussian analyses allow mean differences to be partitioned into two components: one that reflects distributional shifting and one that reflects distributional skewing.…”
Section: Utility Of Distributional Analyses and Cross-task Convergencementioning
confidence: 99%